Virtual Classroom Proficiencies Required by Business Education Lecturers in Colleges of Education in North East Nigeria - Chinwendu L. Nwachukwu; Mohammed Jamilu Usman; Florence Lazarus Bitrus (Jurnal Genesis Indonesia, 2023)
This study examined the virtual classroom proficiencies required by Business Education lecturers in Colleges of Education in North East Nigeria. The study adopted a descriptive survey research design. The study's population was 252, which included 218 lecturers and 34 ICT experts from five colleges of education in Nigeria's North East, with Borno state exempted due to security concerns. Because there was no sampling, the entire population was used for the study due to its manageable size. Data was collected using a validated questionnaire. The instrument was validated by experts. A reliability coefficient was calculated using the Cronbach Alpha technique and a reliability index of 0.89 was achieved after a trial test of the instrument on 10 lecturers and eight ICT Experts. Data for the research questions were analyzed using mean statistics and the hypotheses were tested at a 0.05 level of significance using t-test. The findings revealed lecturers lack proficiency in the use of available participant panel features in a virtual classroom as well as they were not proficient in the use of video play features of the virtual classroom.